Comparison of social enterprises between Malaysia and Singapore / Tan Xiao Jun - Tan , Xiao Jun (2018)
This paper examines the experience and characteristics of social enterprises in Malaysia and Singapore by looking into the fundamental elements underpinning the existence of social enterprise, the factors leading to growth and development of social enterprise and the challenges faced. Qualitative research approach and case study method is adopted where four well-recognized and award-winning social enterprises are selected each in both countries for this study. The data are retrieved from the transcription of interviews with social entrepreneurs as well as via documentation through media and company’s profile and the data analysis adopts the cross case synthesis method. The findings show that the fundamental elements underpinning existence of social enterprises in two countries are their clear missions that are supported by robust business model such as feefor- service, service subsidization and employment business model. Besides, the common indicators for individual factor which are motivation, managerial background and leadership or managerial skill contributes to the growth of social enterprises. On the other hand, the common indicators in organization factors are persistence in retaining mission, flat organization structure, emphasis on internal training and informal performance monitoring. The social and institutional environmental factors in both countries contribute to the development via grants, partnerships, advices and business opportunities. Public acceptance however, is found to be less of a critical environmental indicator in both countries. The common challenges faced by the countries are cash flow, talent acquisition and communicating value of products and services. In general, it is found that Singapore’s social entrepreneurship is a step forward whereby education sector play significant role in development of social enterprise sector, more involvement and partnership of government agencies and ministries with social enterprises in Singapore as well as the research and attempt in developing formal system in performance monitoring. The study contributes by its policy recommendation as well as it serves as an insight to the younger generation and government in better knowing the state of social enterprises sector in both countries.